Pressure Drop Reduction in Fluid Flows with a Polymer Solution - EDOMWONYI-OTU, Lawrence Chukwuka (Engineering Transactions, 2020)
This work is targeted at making available some data to enhance the development of better predictive models for drag reduction (DR) in two-phase flows. Oil-water flows studies were carried out by using a horizontal acrylic pipe (14 mm ID) with tap water and a middle distillate oil the flowing liquids. A hydrolysed polyacrylamide served as the polymer in the water phase. Polyethylene oxide (PEO) with two different molecular weights was equally investigated. At an optimal polymer concentration of 20 ppm, drag was lowered as Reynolds number increased. While drag reduction was effectively described by models, it increased with polymer weight.